Blockchain financialization, neo-colonialism, and Binance - Jutel, Olivier (Frontiers in Blockchain, 2023)
This article will look at the financial geographies and legacies of neo-colonialism to critique the emergence of blockchain financialization in the developing world. Blockchain “financialization” advances through the interplay of crypto imaginaries, new platform economies, and the trading infrastructure for highly leveraged financial products. The largest cryptocurrency exchange, Binance, has presented itself as a champion of the blockchain for development paradigm in Africa. Its success in the region relies on the use of community leaders, hackathons, and the lobbying of governments for regulatory concessions. Binance operates on two scales. Firstly, it is part of a fintech vanguard attempting to dismantle New Deal financial regulatory systems in the Global North (Omarova, Yale Journal on Regulation, 2019, 36, 735–793; Allen, H, DeFi: Shadow Banking 2.0?, 2022). Secondly, it as an agent of financialization in the developing world, promoting DeFi to map the speculative micro-financial practices of the Global South. Crypto and blockchain thus represent extensions of “subprime empire” (Schuster, Current Anthropology, 2021, 62, 389–411) in which marginal economic activities in fragile developing world contexts feed into the North-South extraction of value. This article will outline Binance’s forays into Nigeria as an example of the micro and macro scales of neocolonial finance and the interplay of infrastructure, territory, and the social imaginary in blockchain.